Controllable multi-mode absorption in terahertz absorber with graphene-dielectric-stack strips. (February 2021) - Bian, Li-an; Hong, Yingjie; Li, Congwu; Liu, Yu; Wang, Yaokun; Huang, Kaicheng
Abstract: Multiple near-unity absorption modes are achieved by employing the graphene-dielectric-stack (GDS) strips. Through exciting the surface plasmon polaritons (SPP) resonance and the Fabry-Pérot (FP) resonance, the magnetic field is enhanced at graphene and the near impedance matching is obtained. It is found through the simulation method of rigorous coupled-wave analysis (RCWA) that different modes have distinct sensitivity against the change of the chemical potential of graphene, the geometric parameters of absorption structure along with the angle of incident light, since these modes relay on various resonances in varying degrees. Based on this, all of the modes number, the bandwidth and the peak-peak distance between different modes are controllable. The proposed functional device has tremendous potential applications in the terahertz range, such as multi-channel modulator, photoelectric detection and imaging. Highlights: Multiple near-unity absorption modes are achieved by employing the graphene-dielectric-stack strips. These modes stem from the combined action of SPP resonance and FP resonance. All of the modes number, the bandwidth and the peak-peak distance between modes are controllable. This proposed absorber can be used for thermal power generation, photoelectric detection and imaging.